2004
DOI: 10.1177/160940690400300402
|View full text |Cite
|
Sign up to set email alerts
|

Developing Culturally Competent Health Knowledge: Issues of Data Analysis of Cross-Cultural, Cross-Language Qualitative Research

Abstract: There is a growing awareness and interest in the development of culturally competent health knowledge. Drawing on experience using a qualitative approach to elicit information from Mandarin-or Cantonese-speaking participants for a colorectal cancer prevention study, the authors describe lessons learned through the analysis process. These lessons include benefits and drawbacks of the use of coders from the studied culture group, challenges posed by using translated data for analysis, and suitable analytic appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 51 publications
0
62
0
1
Order By: Relevance
“…Furthermore, respondent validation was carried out with a randomly selected participant, in line with best practice. [43][44][45][46] However, translation has negligible effects on qualitative analysis when conducted within the native language and culture of researchers. [45] Furthermore, the framework approach to data management ensures systematic, rigorous and transparent qualitative data analysis.…”
Section: Data Management Analysis and Trustworthinessmentioning
confidence: 99%
“…Furthermore, respondent validation was carried out with a randomly selected participant, in line with best practice. [43][44][45][46] However, translation has negligible effects on qualitative analysis when conducted within the native language and culture of researchers. [45] Furthermore, the framework approach to data management ensures systematic, rigorous and transparent qualitative data analysis.…”
Section: Data Management Analysis and Trustworthinessmentioning
confidence: 99%
“…A recent study further suggested that having only insider researchers analyzing data may result in shortcomings. Specifically, Tsai et al (2004) found that "outsider" coders tended to raise questions about the meanings of words, whereas insider coders did not. They suggested that insider coders may have been so well acquainted with the behaviors and concepts shared by participants that it prevented them from identifying relevant and unique cultural concepts.…”
Section: Measurementmentioning
confidence: 99%
“…It is often assumed that "insider" researchers are more capable and effective in research with ethnic minorities. In many cases, however, bilingual staff may differ greatly from the study population because of their varied socioeconomic backgrounds and immigration histories (Tsai et al, 2004). Therefore, some argue that cultural matching of researchers/staff and study participants does not necessarily ensure culturally competent research; rather, the most important characteristic in this relationship is the cultural responsiveness of the researchers (Sawyer et al, 1995).…”
Section: Recruitment and Retentionmentioning
confidence: 99%
“…Therefore, the translator needed to be skilled in finding ways to convey concepts from one language into another (Tsai, et al, 2004), particularly with regard to making decisions about the cultural meanings which language carries (Temple & Edwards, 2002). Tsai, et al (2004) suggest that the more knowledgeable researchers are about the cultural beliefs and value orientations of the interviewees, the better able they will be in their interpretations and translations of meaning. From this point of view, the translator is pivotal to cross language research because communication across many languages involves more than just a literal transfer of words.…”
Section: The Research Methodsmentioning
confidence: 99%